Effectiveness of the PjBL-STEAM-IC model in improving students’ environmental awareness in coastal schools - Srilesnawati Lalusu; Elya Nusantari; Frida Maryati Yusuf; Abubakar Sidik Katili; Hartono Mamu; Muhammad Rifai Katili; Masra Latjompoh (Universitas Papua, 2026)
Coastal ecosystem degradation in Pagimana District, combined with science instruction that remains largely theoretical, underscores to the need for a learning model that can foster students’ environmental awareness more comprehensively. This study examined the effectiveness of the PjBL-STEAM-IC model in improving students’ environmental awareness in coastal schools across the four KABS dimensions: knowledge, attitude, behavior, and skills. The study was part of a Research and Development project and specifically reports the field-testing phase, which included limited trials, wider trials, and operational implementation. Participants were 150 seventh-grade students from four coastal junior high schools in Pagimana District. Data were collected using an environmental awareness questionnaire and analyzed using descriptive statistics, N-gain, the Wilcoxon Signed-Rank Test, and the Kruskal-Wallis Test. The results showed that the PjBL-STEAM-IC model effectively improved students’ environmental awareness across all four dimensions. The mean score increased from 67.41 before implementation to 86.81 after implementation, with N-gain values ranging from 0.62 to 0.64, and all dimensions showed significant differences (p < 0.001). These findings suggest that the PjBL-STEAM-IC model is a promising contextual science learning alternative for strengthening environmental awareness in coastal schools.